1999
DOI: 10.1302/0301-620x.81b6.9634
|View full text |Cite
|
Sign up to set email alerts
|

Radiological factors influencing femoral and acetabular failure in cemented Charnley total hip arthroplasties

Abstract: We have made a retrospective review of 185 cemented Charnley total hip arthroplasties performed between 1970 and 1974 to determine the relationships between radiological variables and failure of the femoral and acetabular components. We measured the acetabular wear, the orientation of the cup, the thickness and consistency of acetabular and femoral cement mantles, radiolucency and femoral alignment. The mean follow-up was for 11.7 years. Femoral loosening was demonstrable radiologically in 15 hips (8.1%), ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 16 publications
1
22
0
4
Order By: Relevance
“…Equally, despite the lack of significant difference in implant survivorship, the study demonstrated consistently better patient reported outcomes. The study by Flivik et al26) also reiterated an important point demonstrated in our results and reported by several previous authors343536) which is presence of early radiolucent lines as an accurate predictor of long-term loosening in cemented acetabular component fixation. Such observations are in agreement with earlier results of late aseptic loosening from retrieval analysis33).…”
Section: Discussionsupporting
confidence: 87%
“…Equally, despite the lack of significant difference in implant survivorship, the study demonstrated consistently better patient reported outcomes. The study by Flivik et al26) also reiterated an important point demonstrated in our results and reported by several previous authors343536) which is presence of early radiolucent lines as an accurate predictor of long-term loosening in cemented acetabular component fixation. Such observations are in agreement with earlier results of late aseptic loosening from retrieval analysis33).…”
Section: Discussionsupporting
confidence: 87%
“…The presence or absence of graft incorporation in each of these zones was recorded according to the system described by the Oswestry group (Aulakh et al 2009). Components were considered to have migrated if they had moved by 3 mm or more from the inter-tear drop line or trans-ischial line where this was obscured (Ritter et al 1999). The grade of heterotopic ossification, according to the system of Brooker et al (1973), and the presence of BoneSave in the soft tissues were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Optimizing the mechanical interlock at the bone-cement interface can be achieved by ensuring good cement penetration secondary to good pressurization 4041424344. Experiments in Exeter45 and elsewhere,4647 confirmed that improved cementing is associated with better postoperative radiographs.…”
Section: Optimum Cementing Techniquementioning
confidence: 97%